Improvement in teacher performance following the implementation of school leadership mentoring in a public educational institution in Iquitos, Peru - Zambrano, Jhosiveth (2026)
Educational quality depends on teacher performance and school leadership mentoring; however, weaknesses in pedagogical monitoring, resistance to innovation, and limited systematic feedback persist. The objective was to verify the improvement in teacher performance following the implementation of school leadership mentoring in a public educational institution in Iquitos, Peru. A quantitative approach was used, with a single-group pre-experimental design and pre-test and post-test measurements. The census sample included 36 teachers, to whom a questionnaire, observation sheet, and rubric were applied to collect information on teacher performance. Descriptive analysis showed an improvement in teacher performance after the intervention, shifting from 97.2% at the lowest level and 2.8% at the intermediate level in the pre-test to a distribution concentrated at higher levels in the post-test, with 30.6% at the highest level and 52.8% at the intermediate level, reflecting a marked change in the frequency of the practices assessed. In inferential analysis, Shapiro–Wilk indicated non-normality in the pre-test (p = 0.006) and post-test (p = 0.018); therefore, the Wilcoxon test was applied (α = 0.05), finding significant differences across all dimensions and in the total score (p < 0.001; overall Z = −5.201), with higher scores after the intervention. It is concluded that the professional development strategy oriented toward school leadership mentoring yielded positive results even in contexts with limited training resources, suggesting its contribution to reducing educational quality gaps and to sustaining reflective and collaborative pedagogical leadership practices.